1987
DOI: 10.1182/blood.v70.3.721.bloodjournal703721
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix of cultured bovine aortic endothelial cells contains functionally active type 1 plasminogen activator inhibitor

Abstract: The extracellular matrix (ECM) of cultured bovine aortic endothelial cells (BAEs) was analyzed by immunoblotting and reverse fibrin autography and shown to contain type 1 plasminogen activator inhibitor (PAI-1). Most PAI-1 in the ECM formed complexes with exogenously added tissue-type plasminogen activator (tPA), demonstrating that this PAI-1 was functionally active. The resulting tPA/PAI-1 complexes were recovered in the reaction solution, indicating that the PAI-1 in such complexes no longer bound to ECM. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Forced inhibition of PAI-1 expression decreased cellular PAI-1 antigen and increased uPA activity, whereas secreted PAI-1 and uPA activity did not change, and the level of secreted uPA in PAI-1 − cells is similar to that in control cells. These results may suggest that PAI-1 produced in cancer cells leaves the cells and inactivates secreted uPA protein first, and then free PAI-1 returns to the cancer cell surface and inactivates cell-bound uPA, supporting the theory proposed by Mimuro et al 23) that PAI-1 has a high affinity for some constituents of the ECM and once bound to the ECM, has a longer half life. Moreover, our results may also suggest that the induction of high levels of PAI-1 in cancer cells is necessary to inhibit cell-bound uPA and consequent cellular uPA activity and degradation of the ECM around cancer cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Forced inhibition of PAI-1 expression decreased cellular PAI-1 antigen and increased uPA activity, whereas secreted PAI-1 and uPA activity did not change, and the level of secreted uPA in PAI-1 − cells is similar to that in control cells. These results may suggest that PAI-1 produced in cancer cells leaves the cells and inactivates secreted uPA protein first, and then free PAI-1 returns to the cancer cell surface and inactivates cell-bound uPA, supporting the theory proposed by Mimuro et al 23) that PAI-1 has a high affinity for some constituents of the ECM and once bound to the ECM, has a longer half life. Moreover, our results may also suggest that the induction of high levels of PAI-1 in cancer cells is necessary to inhibit cell-bound uPA and consequent cellular uPA activity and degradation of the ECM around cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…The role of PAI-1 in tumor progression, especially in invasion and metastasis, is still a subject of controversy, and it has been concluded that PAI-1 can be effective in controlling metastasis, depending on the type and location of the primary tumor. Although PAI-1 suppresses uPA activities and ECM degradation in colon cancer, prostate cancer and melanoma, 16,17,23) the role of PAI-1 in invasion and proliferation of HCC cells has not been reported. Our data showed that forced inhibition of PAI-1 increased the invasion index of HCC cells and suggested that the imbalance between uPA and PAI-1 expression and the consequent uPA activity in cancer cells may be important for the invasion of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These results are relevant to other work that emphasizes the importance in the regulation of PA activity of the specific inhibitor, PAI-1 (Gelehrter et al, 1987;Seifert and Gelehrter, 1978;Andreasen et al, 1986Andreasen et al, , 1990Gelehrter, 1989, 1990). PAI-1 is bound to vitronectin in the extracellular matrix and retains its functional activity there (Mimuro et al, 1987;Sakata et al, 1988;Salonen et al, 1989), thereby limiting extracellular proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that because of the presence of a specific receptor for uPA (Roldan et al, 19901, the action of uPA would be confined to the limited space around the uPA receptor after release of the inactive precursor single-chain uPA. The regulated production of PAI-1 would inhibit activities of both tPA and uPA, in the latter case possibly by means of PAI-1 located in the extracellular matrix in which the uPA target cells are lying (Mimuro et a]., 1987;Sakata et al, 1988;Salonen et al, 1989;Ciambrone and McKeown-Longo, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This relation is independent of body mass (Juhan- Vague et al, 1989) and may reflect insulin stimulated hepatic PAI-1 production (Kooistra et al, 1989). PAI-1 and the plasminogen system is of particular interest in patients with PCOS, a condition characterized by anovulation and ovarian connective tissue abnormalities, as this system is intimately involved in ovarian follicle development and connective tissue remodelling (Mimuro et al, 1987).…”
mentioning
confidence: 99%